Measuring the effectiveness of a short interactive module on phishing detection among secondary school students - Jakab Enikő; Якоб Еніке (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Phishing attacks pose a significant and growing threat to the digital safety of secondary school students. As young people increasingly rely on digital technologies for learning, communication, and entertainment, they are frequently exposed to manipulation attempts that aim to exploit their inexperience and trust. Phishing is recognized as one of the most widespread cybersecurity risks affecting adolescent users (Impact Networking, 2024), manifesting through various channels that are part of their daily digital routines — such as fake in-game offers, fraudulent discount links, or social media scams impersonating influencers, peers, or trusted services. These deceptive practices often aim to extract login credentials, financial data, or personal information that can later be misused for identity theft or further targeted cyberattacks. Research indicates that adolescents’ cybersecurity awareness and critical evaluation skills are often insufficient to effectively identify manipulation attempts (Hadlington & Murphy, 2018), and simple warnings alone do not effectively prevent deception in social engineering attacks (Junger et al., 2017). This reveals the need for practical, age-appropriate educational interventions that strengthen students’ ability to recognize suspicious content and make safer decisions online. The aim of this study is to determine whether a short (maximum 20-minute), interactive educational module can improve students’ ability to detect phishing attempts across commonly used digital platforms. Two groups of students are compared: one participates in the interactive education, while the other does not. Students’ performance is assessed before and after the lesson to detect improvement. The research involves students from grades 9–11 and focuses on two key performance aspects: the accuracy of phishing recognition and the quality of justifications provided for their decisions. The intervention uses real examples that are relevant to students’ everyday online activities, and it includes short interactive decision-making tasks with immediate feedback to help them learn how to stay safe online.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: phishing; cybersecurity; interactive learning; informatics education; digital competence development; cybersecurity awareness